Relationship of VDR and VDBP gene polymorphisms with sepsis susceptibility and prognosis - Lian, Chan; Ying, Kangtai; Shao, Haiyan; Gu, Haiting; Mao, Wenwei (Frontiers in Genetics, 2025)
ObjectiveThis research focused on the association of vitamin D receptor (VDR) and vitamin D binding protein (VDBP) gene polymorphisms with sepsis susceptibility and prognosis.Methods110 septic patients were selected as the sepsis group, and another 100 patients with common infections who did not develop sepsis as the control group. 28 days death of patients in the sepsis group were counted. Within 24 h of admission, patients were scored by Acute Physiology and Chronic Health Evaluation Ⅱ (APACHE Ⅱ) and Sequential Organ Failure Assessment (SOFA). Serum lactate (Lac), C-reactive protein (CRP), procalcitoninogen (PCT) and vitamin D levels were evaluated. All patient DNAs were extracted. The polymorphisms of VDR and VDBP genes and vitamin D genes Fok Ⅰ (rs2228570) and VDBP rs4588 locus were tested and compared in both groups; and the receiver operating characteristic (ROC) curves were plotted to calculate the area under the area under the curve (AUC) and assess the diagnostic value of each indicator for sepsis. Patients in the sepsis group were categorized into a death group and a survival group, the above indicators were compared in the two groups and the factors affecting the prognosis of sepsis patients were analyzed.ResultsCompared to the control group, the sepsis group exhibited higher APACHE II scores, SOFA scores, serum Lac, CRP, PCT levels, VDR Fok Ⅰ (rs2228570) locus f allele and VDBP rs4588 locus A allele frequencies, and lower vitamin D levels (P < 0.05). The ROC curve analysis showed that the AUC for the diagnosis of sepsis using the AA genotype at the VDBP gene rs4588 locus was 0.579 (95% CI: 0.501–0.656) (sensitivity: 52.70%; specificity: 63.00%, P < 0.05). APACHE II and SOFA scores and serum levels of Lac, CRP, and PCT in the death group were raised and vitamin D levels were diminished than those in the survival group (P < 0.05). Raised APACHE II and SOFA scores were independent risk factors affecting sepsis prognosis.ConclusionThe f allele at the VDR Fok Ⅰ (rs2228570) locus and the A allele at the VDBP rs4588 locus significantly raise the risk of sepsis in patients.